Q: How do you simplify 3x to the power of 2 plus x plus 2x to the power of 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

3x(2x + 1) over (2x - 1)(2x + 1) Cancel out the 2x + 1 Answer: 3x/2x - 1

5x - 8a + 4a - 2x + a = 3x - 3a

simplify it, 7x-12=x+2+2x-3x 7x=2+12+3x-3x 7x=14 x=2

2x + 3x = 5x

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

Related questions

3x + 7y

3x(2x + 1) over (2x - 1)(2x + 1) Cancel out the 2x + 1 Answer: 3x/2x - 1

5x - 8a + 4a - 2x + a = 3x - 3a

simplify it, 7x-12=x+2+2x-3x 7x=2+12+3x-3x 7x=14 x=2

3x-2y+9+9y-x = 2x+7y+9

3x + 2x - 8x + 2x = -x

2x + 3x = 5x.

2x + 3x = 5x

3x2 + 2x - 8 = 3x2 + 6x - 4x - 8 = 3x(x + 2) - 4(x + 2) = (x + 2)(3x - 4).

Right, 3x-4x+9x-x1. 3x - x = 2x2. 9x-4x = 5x- 2x +5x = 7x

6x^2

2x+3x = 5x